High Eddington quasars as discovery tools: current state and challenges - Panda, Swayamtrupta; Marziani, Paola (Frontiers in Astronomy and Space Sciences, 2023)
A landmark of accretion processes in active galactic nuclei (AGN) is the continuum originating from a complex structure, i.e. an accretion disk and a corona around a supermassive black hole. Modelling the broad-band spectral energy distribution (SED) effectively ionizing the gas-rich broad emission line region (BLR) is key to understanding the various radiative processes at play and their importance that eventually leads to the emission from diverse physical conditions. Photoionization codes are a useful tool to investigate two aspects, the importance of the shape of the SED, and the physical conditions in the BLR. In this work, we critically review long-standing issues pertaining to the SED shape and the anisotropic continuum radiation from the central regions around the accreting supermassive black holes (few 10-100 gravitational radii), with a focus on black holes accreting at high rates, possibly much above the Eddington limit. The anisotropic emission is a direct consequence of the development of a geometrically and optically thick structure at regions very close to the black hole due to a marked increase in the accretion rates. The analysis presented in this paper took advantage of the look at the diversity of the type-1 AGN provided by the main sequence of quasars. The main sequence permitted us to assess the importance of the Eddington ratio and hence to locate the super Eddington sources in observational parameter space, as well as to constrain the distinctive physical conditions of their line-emitting BLR. This feat is posing the basis for the exploitation of quasars as cosmological distance indicators, hopefully allowing us to use the fascinating super Eddington quasars up to unprecedented distances.